2005
DOI: 10.1111/j.0022-202x.2005.23885.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis-Like Mitochondrial Impairment Triggers Antioxidant and Bcl-2-Dependent Keratinocyte Differentiation

Abstract: Terminally differentiated keratinocytes are dead enucleated squams. We showed previously that the mitochondria-dependent cell death pathway might be gradually activated as differentiation progresses. In this study, we demonstrated that protoporphyrin IX, staurosporine, and rotenone induced apoptotic-like changes in the mitochondria, and early differentiation of keratinocytes without inducing apoptosis. Kinetics studies established that differentiation-related changes, including growth arrest, flattened morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 56 publications
4
25
0
Order By: Relevance
“…Our data reveal increases in ROS production in both iASPP-silenced and differentiated keratinocytes. Previous studies have established that differentiationrelated changes, including induction of a flattened morphology, stratification and keratin-10 expression, were a consequence of ROS production (Tamiji et al, 2005). Our findings identify that UV-B exposure promotes the appearance of differentiation markers in keratinocytes.…”
Section: Discussionsupporting
confidence: 64%
“…Our data reveal increases in ROS production in both iASPP-silenced and differentiated keratinocytes. Previous studies have established that differentiationrelated changes, including induction of a flattened morphology, stratification and keratin-10 expression, were a consequence of ROS production (Tamiji et al, 2005). Our findings identify that UV-B exposure promotes the appearance of differentiation markers in keratinocytes.…”
Section: Discussionsupporting
confidence: 64%
“…The signaling pathways associated with this phenomenon are incompletely understood. However, mitochondrial oxidative stress was shown to promote epidermal differentiation in mice (40) and in culture (41), as did uncoupled mitochondria (42). Our studies of constitutive Sod2-deficient mice also showed increased keratinocyte differentiation (19), but early lethality complicated interpretation of this result.…”
Section: Discussionmentioning
confidence: 61%
“…The latter was further supported by observation of correlation between ROS concentration and degree of keratinocyte differentiation (41,42). We therefore hypothesized that eTRPM8-dependent production of both ATP and O…”
Section: Suppresses Omentioning
confidence: 63%